Transplantation of carica (Vasconcellea pubescens) at various altitudes of Mount Lawu, Central Java with treatment of shade and different types of fertilizers - ALFATIKA PERMATASARI; SUGIYARTO SUGIYARTO; MARSUSI MARSUSI; HAILU WELDEKIROS HAILU (Smujo International, 2015)
Abstract: Permatasari A, Sugiyarto, Marsusi, Hailu WH. 2015. Transplantation of carica (Vasconcellea pubescens) at various altitudes of Mount Lawu, Central Java with treatment of shade and different types of fertilizers. Nusantara Bioscience 7: 6-14. Ex-situ conservation efforts to increase crop production can be done by means of transplantation. The aim of this study was to assess the effect of altitude, shade, and type of fertilizer and their interactions to the performance of carica (Vasconcellea pubescens) vegetative plants transplanted to Mount Lawu, Central Java, Indonesia. The research was conducted in divided plot design at three altitudes (± 1400, 1600 and 1800 m asl.) with shade treatment as main plots and fertilizer (manure, Zwavelzuur ammonium/ZA fertilizer, combination of manure with Ammonium fertilizer, and control) as subplots. Parameters of vegetative variability were observed. The results of the performance of carica vegetative plant were analyzed using ANOVA followed by Duncan's test at 5% standard test. It was observed that an increase in altitude caused slower growth of carica vegetative parts, but better vegetative growth performance in the presence of shade. For the fertilizers, the best growth parameters were obtained in the treatment of manure with ZA fertilizer. Interaction between altitude, shade, and type of fertilizer significantly influenced the performance of carica vegetative parameters. The best growth parameters are at an altitude of 1400 m above sea level with shade treatment and manure combined with ZA fertilizer.